2020
DOI: 10.1038/s42005-020-00471-6
|View full text |Cite
|
Sign up to set email alerts
|

Driving positron beam acceleration with coherent transition radiation

Abstract: Positron acceleration in plasma wakefield faces significant challenges, as the positron beam must be pre-generated and precisely coupled into the wakefield and, most critically, suffers from defocusing issues. Here we propose a scheme that utilizes laser-driven electrons to produce, inject, and accelerate positrons in a single setup. The high-charge electron beam from wakefield acceleration creates copious electron–positron pairs via the Bethe–Heitler process, followed by enormous coherent transition radiation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…The target fills the simulation window in the transverse direction. The consistence of simulation and theoretical results [22] confirmed that the CTR field induced by the target is the same as that induced by an infinite target. In real experiment, one can always utilize a transversal large enough target to avoid the influence of finite transverse size [44,45].…”
Section: Particle-in-cell Simulationssupporting
confidence: 53%
See 2 more Smart Citations
“…The target fills the simulation window in the transverse direction. The consistence of simulation and theoretical results [22] confirmed that the CTR field induced by the target is the same as that induced by an infinite target. In real experiment, one can always utilize a transversal large enough target to avoid the influence of finite transverse size [44,45].…”
Section: Particle-in-cell Simulationssupporting
confidence: 53%
“…Another novel and promising positron acceleration scheme relies on coherent transition radiation (CTR) [22], which has recently been experimentally demonstrated in relativistic electron acceleration [23]. Intense CTR generates naturally when the driving electron beam passes through the rear surface of high-Z target, captures and accelerates the generated positrons into high energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrashort THz field waveforms help coherently control over the dynamics of spins 14 , molecular rotations 9 , 15 , 16 , vibrations of crystal lattices 17 , and evolution of free- and bound-state electron wave packets 9 13 , 18 . In strong-field ultrafast optics, THz generation provides means for particle acceleration 19 , laser-wakefield characterization 20 , 21 , external-field-assisted high-harmonic generation 11 13 , 22 , and electron bunch diagnostics at particle-accelerator, synchrotron, and free-electron laser (FEL) facilities 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerical studies have explored the potential for gamma-ray emission [28][29][30][31] and positron creation [32][33][34][35]. To date, only three schemes for positron creation and acceleration have been proposed [36][37][38].…”
mentioning
confidence: 99%